Defining Green Accounting in the Health Sector: West Lombok District Health Center - Fathurrahman Kurniawan; Wahidatul Husnaini (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effect of total quality management (TQM), supply chain management (SCM) on Operational performance mediated by competitive advantage. This approach uses a quantitative approach. The population in this study was workers and partners in the oil and gas sector. The data analysis technique used was non-probability sampling with a purposive sampling technique. The results of this study are Total Quality Management(TQM) has a positive effect on Operational Performance (OP), Supply Chain Management (SCM) has a positive effect on Operational Performance (OP), TQM has a positive effect on Competitive Advantage (CA), SCM has a positive effect on CA, Competitive Advantage (CA) on Operational Performance (OP) has a significant positive relationship, is statistically significant, there is a significant positive effect of Supply Chain Management (SCM) on Operational Performance through Competitive Advantage mediation. Theoretically, this research enriches the scientific references on the relationship between the implementation of TQM, SCM, and operational performance, especially in the context of the oil and gas industry, and adds a new perspective on how competitive advantage acts as a mediator in the relationship. And practically, it identifies the most relevant and effective TQM and SCM practices for oil and gas companies in achieving sustainable competitive advantage.